Prototype Penggunaan IoT untuk Monitoring Level pada Penampung Air Berbasis ESP8266 - Steven Sachio; Agustinus Noertjahyana; Resmana Lim (Jurnal Infra, 2017)
Nowadays, almost all communication using internet, but is not all, now object also can communicating each other, this concept is calls Internet of Things (IoT). Things in IoT can be everything that we use every day. In this journal, the thing is water container or in Indonesia it calls ”bak mandi”. Why water container? Because, after we use water in the water container usually the level of the water container is reduced and we must fill it up for other people that use the water container. Usually in the process of filling the water container, we forgot to close the valve or pump so water is overflowing and the water is wasted. This is why we thought using the Internet of Things concept can solve the problem. In our solution is make a device or module that can monitoring level of the water container. That device or module can open and close the pump or valve automatically so water not overflowing and wasted. To make device or module that can generate level of the water container we use ultrasonic sensor. But that bring up hypothesis: could ultrasonic sensor read level of water container and how good the accuracy?